2020
DOI: 10.1590/1518-8345.3946.3357
|View full text |Cite
|
Sign up to set email alerts
|

Application of the educational method of realistic simulation in the treatment of pressure injuries

Abstract: Objective: to evaluate the use of realistic simulation as a strategy to promote teaching about pressure injuries. Method: This is a quasi-experimental study. A modified and translated version of the Pieper Pressure Ulcer knowledge test was applied. Kappa statistical analysis was used to assess the professionals’ knowledge in the realistic simulation using the SPSS software. A p-value <0.05 was considered significant. Results: Seventy-seven nursing professionals participated in the realistic simulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…This indicates that nurses should have consistent knowledge of wounds and wound care to deliver evidence-based care. The literature has shown that nurses' wound care knowledge, such as pressure ulcer knowledge, is limited and that education on wound care is unstructured at the undergraduate level and in continuing education [24,25].…”
Section: Of 12mentioning
confidence: 99%
“…This indicates that nurses should have consistent knowledge of wounds and wound care to deliver evidence-based care. The literature has shown that nurses' wound care knowledge, such as pressure ulcer knowledge, is limited and that education on wound care is unstructured at the undergraduate level and in continuing education [24,25].…”
Section: Of 12mentioning
confidence: 99%
“…Estudos demonstram que a estratégia educativa é um meio eficaz para a melhoria do conhecimento sobre LP e a mudança de comportamento dos profissionais na prática de enfermagem, sobretudo em se tratando de um marcador de qualidade do atendimento no qual os enfermeiros desempenham um papel essencial 24,25…”
Section: Resultsunclassified
“…Saudi Arabian universities should adopt simulation-based approaches to prepare nursing students and help them acquire the required knowledge and skills regarding pressure injury prevention and management. Adapting such an approach to educating nursing students may be important, as it provides the opportunity to experience a real situation in managing patients with such conditions and helps increase their knowledge and skills regarding pressure injury management and prevention ( Baracho et al, 2020 ; Mazzo et al, 2017 ; Sezgunsay & Basak, 2020 ).…”
Section: Discussionmentioning
confidence: 99%